2020
DOI: 10.1002/jee.20350
|View full text |Cite
|
Sign up to set email alerts
|

Engineering mindsets and learning outcomes in elementary school

Abstract: Background: Students may exhibit growth mindsets, where intelligence is seen as malleable and failures prompt more effort and new approaches, or fixed mindsets, where intelligence is seen as immutable and failures indicate lack of intelligence. One's mindset in general may be different from that for a particular domain such as engineering. Having a growth mindset predicts more positive learning outcomes. Purpose: We described the general and engineering mindsets of students in fifth-grade U.S. classrooms (ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
(89 reference statements)
1
14
0
Order By: Relevance
“…Their findings revealed that a general growth mindset was a strong predictor of a growth engineering mindset, which they defined as a disposition toward obtaining engineering skills and becoming a successful engineer. Lottero‐Perdue and Lachapelle (2020) emphasized that adopting a growth engineering mindset is crucial to being productive in engineering design.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their findings revealed that a general growth mindset was a strong predictor of a growth engineering mindset, which they defined as a disposition toward obtaining engineering skills and becoming a successful engineer. Lottero‐Perdue and Lachapelle (2020) emphasized that adopting a growth engineering mindset is crucial to being productive in engineering design.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students were more likely to have a more growth-minded engineering mindset score if they had a higher socioeconomic status, did not receive special education services, experienced more wholeclass discussion and activity, or had a higher growth mindset score. Low SES students and special education students had lower engineering mindset scores (Lottero-Perdue & Lachapelle, 2020).…”
Section: Table 2 Summary Of K-8 Stem Education Growth Mindset Researchmentioning
confidence: 97%
“…A less positive finding was that low SES students and special education students had lower engineering mindset scores. It is important that teachers and researchers engage in further work on investigating ways to support all students to engage in productive struggle (Lottero-Perdue & Lachapelle, 2020).…”
Section: Growth Mindset In K-8 Stem Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote courses provide students with greater flexibility for organizing their time, and by experiencing this first-hand during the ERT, students may have become aware of new learning possibilities. The research is also aimed at identifying possible correlation between students' opinions and their academic performance, an interesting link that has been studied by several researchers when applied to other situations [33]. Additionally, the research defines student profiles based on the opinion and academic performance combinations.…”
Section: Learning Strategies and Student Profilesmentioning
confidence: 99%